Cross-Culture Analysis: Cultural Adaptation and Nonverbal Communication in Non-Native English-Speaking Countries - Yuli Angraini (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The objectives of the research were (1) to discover which mode of nonverbal communication did visitors most frequently use to communicate with non-native English-speakers countries and vice versa, (2) to know which mode of nonverbal communication did the visitors most rarely use to adapt to non-native English-speakers countries and vice versa, (3) to describe non-native English-speakers’culture when the visitors used nonverbal communication with them. The method of the research was descriptive. The research used content validity. The subjects of the research were 54 people taken from the second semester of Batam Center students of University of Riau Kepulauan majoring in English Education Department consisted of 28 students; 5 non-native English-speakers countries (European one) and 21 online respondents of 204.666 members of Backpacker International public group site. The data were collected through observation and interview then analyzed by SPSS 24 version on the base of Little John’s modes of nonverbal communication (2009). The results of the research were (1) 74.1% (kinesics/body language) was the most frequently used; (2) 75.9% (haptics/touch) was the most rarely used; (3) 180 degree of space when Nns met the visitor for the first time (proxemics/space), Nns barely used the touch unless for specific reason (haptics/touch);often used eye contact when focused on something, punctual (chronemics/time), flat face tended to be cold and rarely used gestures if not necessary (kinesics/body language), in the center city, women were more fashionable, average body liked their height got many benefits (physical environment-appearance). Like all Euroepan, Nns tended to speak faster and not clear enough (paralanguage/vocalics). In brief, the faster visitors could adapt to them the faster NNs opened themselves to the visitors.